Pengaruh Penggunaan Model Pembelajaran Talking Stick Terhadap Minat Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas IX SMP Negeri 1 Sitiotio Tahun Pembelajaran 2023/2024 - Irwan Banjarnahor; Taripar Aripin Samosir; Damayanti Nababan; Simion D. Harianja; Robert K. A Simangunsong (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The aim of this research is to determine whether students' interest in learning about Christian Religious Education and Character Education who are taught using the talking stick learning model is higher than students who are taught without the talking stick learning model in class IX of SMP Negeri 1 Sitiotio for the 2023/2024 academic year. The method used in this research is a quantitative research method with True Experimental design Posttest Only Control statistics. The population is all class IX students of SMP Negeri 1 Sitiotio for the 2023/2024 academic year, totaling 103 people. The sample was determined using a technique taken deliberately (purposive sampling) with the specified conditions that the material being experimented on was in that class, namely class IX-B with 36 people as the experimental class and class IX-C with 7 people as the control class. The research instrument used a 26-item closed questionnaire. The t test used is the separated variance t test according to the analysis requirements, namely n1≠n2 and the variance of the two sample groups is not homogeneous. The results of hypothesis testing obtained a value of t = 11.233 > t table = 2.691, so H0 was rejected and Ha was accepted. This research concludes that there is a higher interest in learning about Christian religious education and character in students who are taught using the talking stick learning model than students who are taught without the talking stick learning model in class IX of SMP Negeri 1 Sitiotio for the 2023/2024 academic year.